2018
DOI: 10.5194/acp-2018-265
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation of the oxidation of methyl vinyl ketone (MVK) by OH radicals in the atmospheric simulation chamber SAPHIR

Abstract: <p><strong>Abstract.</strong> The photooxidation of methyl vinyl ketone (MVK) was investigated in the atmospheric simulation chamber SAPHIR for conditions at which organic peroxy radicals (RO<sub>2</sub>) mainly reacted with NO (<q>high NO</q> case) and for conditions at which other reaction channels could compete (<q>low NO</q> case). Measurements of trace gas concentrations are compar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The rate coefficients for O 2 elimination from NO 3 -isoprene-O 2 radicals are then obtained from the forward O 2 -addition reaction rates and theory-derived equilibrium constants, similar to the approach by Peeters et al 13 More details, the temperature-dependent rate coefficients, and the equilibrium constants are provided in the ESI. † [70][71][72][73] and can be neglected. Ring closure reactions should be divided into three categories: formation of 5-membered peroxide rings with an endo-cyclic alkyl radical site, formation of 5-membered rings with an exo-cyclic radical site, and formation of 6-membered rings (here always with an endo-cyclic radical site).…”
Section: Theoretical Results On the Initial No And O 2 Addition On Ismentioning
confidence: 99%
“…The rate coefficients for O 2 elimination from NO 3 -isoprene-O 2 radicals are then obtained from the forward O 2 -addition reaction rates and theory-derived equilibrium constants, similar to the approach by Peeters et al 13 More details, the temperature-dependent rate coefficients, and the equilibrium constants are provided in the ESI. † [70][71][72][73] and can be neglected. Ring closure reactions should be divided into three categories: formation of 5-membered peroxide rings with an endo-cyclic alkyl radical site, formation of 5-membered rings with an exo-cyclic radical site, and formation of 6-membered rings (here always with an endo-cyclic radical site).…”
Section: Theoretical Results On the Initial No And O 2 Addition On Ismentioning
confidence: 99%
“…Additionally, prior studies also reported that OH regeneration might be achieved from the oxidation of MACR and MVK, which are the major first-generated products of isoprene (Fuchs et al, 2018(Fuchs et al, , 2014. As a potential explanation for the high OH concentration, the impacts of MACR and MVK oxidation were evaluated here.…”
Section: Influencing Factors Of Oh Underestimationmentioning
confidence: 99%
“…The large majority of the alkoxy radicals formed will either decompose or isomerize 13,[58][59][60] and their detectability will be determined by their yield of HO 2 radicals. A recent study on methyl vinyl ketone (MVK), 61 one of the main products from the OH-initiated oxidation of isoprene, showed that only a partial detection of the RO 2 radicals generated was achieved due to the ''slow'' formation of HO 2 radicals.…”
Section: Instrumentationmentioning
confidence: 99%